Design of concrete structures - Darwin, D. Dolan, C.W; Darwin, David (McGraw Hill Publishing, 2020)
"The text presents the basic mechanics of structural concrete and methods for the design of individual members subjected to bending, shear, torsion, and axial forces. It additionally addresses in detail applications of the various types of structural members and systems, including an extensive presentation of slabs, beams, columns, walls, footings, retaining walls, and the integration of building systems"